Learning Nurbs Through S-CAD - Abdullah, Abdul Rahman (Malaysian Journal of Computer Science, 2017)
S-CAD or Simple Computer Aided Design is a CAD software specially design and develop for Senior High School student introduced by the CAD Research Group, Universiti Kebangsaan Malaysia. The software provides most of the functions normally available in CAD systems. This paper introduces the NURBS entity, e.g., the degree value, the knot vector, the control points and weight of control point. Consequently the paper discusses the learning and understanding of this entity using the SCAD.